The Effect Of Workload On Work Productivity With Work Motivation As An Intervening Variable On Employees Of PT. Pelayaran Nasional Indonesia (Persero) Makassar Branch - Azratul Khairiyah Mataho Parange (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to analyze the effect of workload on work productivity, with work motivation as an intervening variable, at PT. Pelayaran Nasional Indonesia (Persero), Makassar Branch. The primary focus of this study is to identify the direct and indirect influences and the most significant factors in increasing work productivity, and how the relationships between these variables influence the maintenance of work productivity. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 34 respondents, employees of PT. Pelayaran Nasional Indonesia (Persero), Makassar Branch. The analytical technique used was path analysis to test the indirect effect of an independent variable on the dependent variable through an intervening variable (the effect of workload on work productivity, with work motivation as the intervening variable). The results indicate that workload has a negative and significant effect on work productivity, workload has no negative and significant effect on work motivation, work motivation has a positive and significant effect on work productivity, and workload has no negative and significant effect on work productivity, with motivation as the intervening variable, among PT. Indonesian National Shipping (Persero) Makassar Branch.